Mapping the global landscape of research on cultural values and moral values: A bibliometric analysis of research evolution and collaboration networks - Saefudin, Saefudin; Kurniawati, Hasni Dyah; Muhammad Islam, Azmi; Gunaasih, Sang Ayu Putu Piastini; Prajnasari, Puspa Ratri; Suprayogo, Dhino (Research Journal in Advanced Humanities, 2026)
Alongside increasing globalization, digitalization, and social change, research on cultural and moral values has grown rapidly. This study aims to map the development of literature in this field using a mixed-methods bibliometric approach. Data were obtained from the Scopus database for the period 1968–2025 and analyzed using RStudio, Biblioshiny, and VOSviewer to identify publication trends, academic collaboration networks, thematic clusters, and research gaps. The analysis results reveal a consistent increase in publications, with international collaboration among the United States, China, and Southeast Asian countries serving as the primary drivers of cross-cultural knowledge exchange and interdisciplinary research development. Three main clusters were identified: the development of basic concepts of cultural and moral values, education and internalization of values in social and gender contexts, and the influence of technology and contemporary social changes on the formation of intergenerational morality. Despite the growth in publications, research on emerging topics such as the influence of social media, big data, and cultural-moral interactions in the digital age remains limited. These findings underscore the importance of interdisciplinary approaches and cross-national collaboration in broadening the understanding of cultural and moral values. This study provides a systematic contribution to the academic landscape of this field and highlights opportunities for further research that is more adaptive, inclusive, and responsive to the social and cultural dynamics of modern global societies.